Mercury Exposure: Protein Biomarkers of Mercury Exposure in Jaraqui Fish from the Amazon Region - Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira [UNESP]; de Oliveira, Grasieli [UNESP]; Padilha, Cilenedo Carmo Federici [UNESP]; de Moraes, Paula Martin [UNESP]; Zara, Luiz Fabricio; Leite, Alinede Lima; Buzalaf, Marília Afonso Rabelo; Padilha, Pedrode Magalhães [UNESP] (Springer Nature, 2018)
This study presents data on the extraction and characterization of proteins associated with mercury in the muscle and liver tissues of jaraqui (Semaprochilodus spp.) from the Madeira River in the Brazilian Amazon. Protein fractionation was carried out by two-dimensional electrophoresis (2D-PAGE). Mercury determination in tissues, pellets, and protein spots was performed by graphite furnace atomic absorption spectrometry (GFAAS). Proteins in the spots that showed mercury were characterized by electrospray ionization tandem mass spectrometry (ESI-MS/MS). The highest mercury concentrations were found in liver tissues and pellets (426 ± 6 and 277 ± 4 μg kg−1), followed by muscle tissues and pellets (132 ± 4 and 86 ± 1 μg kg−1, respectively). Mercury quantification in the protein spots allowed us to propose stoichiometric ratios in the range of 1–4 mercury atoms per molecule of protein in the protein spots. The proteins characterized in the analysis by ESI-MS/MS were keratin, type II cytoskeletal 8, parvalbumin beta, parvalbumin-2, ubiquitin-40S ribosomal S27a, 39S ribosomal protein L36 mitochondrial, hemoglobin subunit beta, and hemoglobin subunit beta-A/B. The results suggest that proteins such as ubiquitin-40S ribosomal protein S27a, which have specific domains, possibly zinc finger, can be used as biomarkers of mercury, whereas mercury and zinc present characteristics of soft acids.
Keywords: 2D-PAGE; Biomarkers of mercury exposure; ESI-MS/MS; Mercury in fish; Metallomics study